INADEQUACIES OF LEGAL FRAMEWORK OF MOSQUE TOURISM TOWARDS DEVELOPMENT OF TOURISM INDUSTRY IN MALAYSIA: A REVIEW - Wong Hua Siong, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Halal or Muslim-friendly tourism is a novel concept in the tourism sector that facilitated new and exciting possibilities for improved financial advancement. Specifically, mosque tourism has become one of the most pertinent areas (an emerging trend under halal tourism) following the rising number of tourists visiting nations with a Muslim-majority population. As such, it was vital to denote the mosque tourism concept and determine subsequent shariah and legal complexities. Additionally, identifying the appropriateness of the laws governing mosque management and visitors proved essential. The current study objectives aim to denote the mosque tourism concept, determine shariah and legal intricacies in mosque tourism, identify visitors’ requirements and satisfaction, examine the appropriateness of the laws governing mosque management and tourists, and recommend a legal framework. This qualitative research encompassed a systematic study involving philosophical and academic perspectives with past works of literature. As this study involved library research from different primary data sources, library studies and critical analyses were employed in assessing pertinent materials, data, and knowledge on Islamic religious tourism, particularly Muslim tourist protection concerns. Figures from relevant governmental agencies (Ministry of Tourism and Culture Malaysia) would be duly measured and analysed. Furthermore, assessments of current laws, regulations, and guidelines on tourists’ legal protection in mosque tourism were also performed. The anticipated resulted served to recommend the most appropriate legal framework to be incorporated in Malaysia to safeguard all stakeholders’ interests in mosque tourism.